SISTEM AQUACULTURE DAN LUNAR HARVESTING SEBAGAI PENERAPAN ARSITEKTUR REGENERATIF PADA PERANCANGAN WISATA KAMPUNG NELAYAN CILINCING - Tengganu, Celine; Komala, Olga Nauli (Jurusan Arsitektur dan Perencanaan, 2025)
Kampung Nelayan Cilincing experiences significant ecological pressure due to the accumulation of plastic waste from urban activities on the coast of North Jakarta. This plastic waste ends up in the ocean and produces microplastics, plastic particles measuring less than 5mm that endanger the marine ecosystem, food chain, and human health. This study aims to optimize Kampung Nelayan Cilincing with the concept of